Analisa Penyakit Jantung Menggunakan Algoritma Naïve Bayes - Andri Nofiar Am; Mahdiawan Nurkholifah; Fenty Kurnia Oktorina (Journal of System and Computer Engineering (JSCE), 2023)
Every year more than 2 million Americans die from heart disease which is the number one killer in the world. The results of the Sample Registration System (SRS) survey show that heart disease is the highest cause of death at all ages after stroke, which is 12.9%. The method used in this study uses the Naïve Bayes algorithm. The purpose of this study is to determine if anyone with heart disease has a stroke. From the research results obtained by splitting data using 80:20 to get a prediction accuracy rate of 83% for heart disease prediction cases. In the trial results using the label test data obtained, namely no stroke.